Pengembangan Media Career Card untuk Kesadaran Karir di SMP Negeri 2 Palangka Raya - Munawarah, Hanikhatul; Singgih, Fendahhapsari; Pan Pangestie, Esty (JURNAL PENDIDIKAN, 2023)
The purpose of this research was to determine the service of career card media and find out whether career card media is useful for student career awareness at SMP Negeri 2 Palangka Raya This research uses a Research and Development (RnD) approach, namely research and development whose final results produce a product, namely a career card for career awareness. The development model used by researchers is adamitated from Born and Gall with 6 stages of development research. Samples were taken using Purposive Sampling Technique so that the sample selection criteria were 8 students from grades VII-7 SMPN 2 Palangka Raya. The main data collection tool used by researchers is questionnaires, researchers provide questionnaires to find out whether or not there are changes before and after the use of career card media for career awareness. Then the data were analyzed using parametric statistics from Kolmogorov-Sminrnov with the help of SPSS 25 with the results of normally distributed data. Researchers end up dancing conclusions based on the results of statistics. The results showed that the t-test calculation using the paired sample t test showed sig. 0.000 < 0.05 and thecalculated t value is compared withthe Tabel t value which is 26.200 > 2.213 then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that there is a significant difference between before and after the use of media career cards for student career awareness.